Unsuccessful vs. successful performance in snatch lifts: A kinematic approach - Gourgoulis, V.; Aggeloussis, N.; Garas, A.; Mavromatis, G. (The Journal of Strength and Conditioning Research, 2009)
The purpose of the present study was to determine the kinematic characteristics of snatch movements that result in an unsuccessful performance, involving the barbell's drop in front of the weightlifter. The sample comprised 7 high-level men weightlifters competing at the international level. Their successful and unsuccessful snatch lifts with the same load were recorded with 2 S-VHS camcorders (60 Hz), and selected points onto the body and the barbell were digitized manually using the Ariel Performance Analysis System. The statistical treatment of the data showed no significant differences (p > 0.05) between successful and unsuccessful lifts in the angular displacement and velocity data of the lower-limb joints, the trajectory and vertical linear velocity of the barbell, or the generated work and power output during the first and second pulls of the lift. Consequently, the general movement pattern of the limbs and the barbell was not modified in unsuccessful lifts in relation to the successful ones. However, significant differences (p < 0.05) were found in the direction of the barbell's resultant acceleration vector, suggesting that proper direction of force application onto the barbell is crucial for a successful performance in snatch lifts. Thus, coaches should pay particular attention to the applied force onto the barbell from the first pull.